Molecular Alterations and Their Correlation With the Survival of Glioblastoma Patients With Corpus Callosum Involvement - Cui, Meng; Gao, Xin; Chi, Yihong; Zhang, Meng; Lin, Hepu; Chen, Hewen; Sun, Caihong; Ma, Xiaodong (Frontiers in Neuroscience, 2021)
Purpose To explore molecular alterations and their correlation with the survival of patients with glioblastoma (GBM) with corpus callosum (CC) involvement (ccGBM). Methods Electronic medical records were reviewed for glioma patients tested for molecular alterations and treated at our hospital between January 2016 and July 2020. ccGBM was compared to GBM without CC involvement (non-ccGBM) to identify differences in molecular alterations. Clinical outcomes and survival were compared between ccGBM and non-ccGBM patients, as well as among patients with ccGBM with different molecular alteration statuses. ccGBM was also compared to diffuse midline glioma (DMG) to clarify their correlation in molecular alterations, the progression-free survival (PFS) and overall survival (OS). Results Thirty ccGBM and 88 non-ccGBM patients were included. PDGFRA amplification (PDGFRAamp, 33.3% versus 9.1%, P=0.004) and missense mutation (PDGFRAmut, 20.0% versus 3.4%, P=0.011) both had higher incidences in ccGBM than in non-ccGBM. PDGFRA alteration was associated with the occurrence of ccGBM (OR=4.91 [95% CI: 1.55-15.52], P=0.007). ccGBM with PDGFRAamp resulted in a shorter median PFS (8.6 versus 13.5 months, P=0.025) and OS (12.4 versus 17.9 months, P=0.022) than non-ccGBM with PDGFRAnon-amp. ccGBM with PDGFRAamp combined with PDGFRAmut (PDGFRAamp-mut) had a shorter median PFS (7.6 versus 8.9 months, P=0.022) and OS (9.6 versus 17.8 months, P=0.006) than non-ccGBM with wild-type PDGFRA and no amplification (PDGFRA-w, non-amp). Compared to ccGBM with PDGFRA-w, non-amp, ccGBM with PDGFRAamp and PDGFRAamp-mut both had a shorter median PFS and OS (P<0.05). The hazard ratios (HRs) of PDGFRAamp for PFS and OS in ccGBM were 3.08 (95% CI: 1.02-9.35, P=0.047) and 5.07 (1.52-16.89, P=0.008), and the HRs of PDGFRAamp-mut for PFS and OS were 13.16 (95% CI: 3.19-54.40, P<0.001) and 16.36 (2.66-100.70, P=0.003). ccGBM may have similar incidences of PDGFRAamp or mut (PDGFRAamp/mut) as DMG, and they also had similar median PFS (10.9 versus 9.0 months, P=0.558) and OS (16.8 versus 11.5 months, P=0.510). Conclusions PDGFRA alterations are significantly associated with the occurrence and poor prognosis of ccGBM. ccGBM with PDGFRAamp/mut may be classified as a single subtype of GBM that has a similar survival rate to DMG. PDGFR inhibitors may be a promising treatment method for ccGBM.